PERAN DALIHAN NA TOLU DALAM MENINGKATKAN PENDIDIKAN IPA PADA ETNOSAINS: PERSPEKTIF FILSAFAT - Gunaria Siagian; Titis Wulandari; Lufri Lufri; Asrizai Asrizai; Hardeli Hardeli (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
A very basic concept in the traditional Toba Batak kinship organization is the clan. Marga is a group of people who come from the same grandfather and follow the lineage from the father which is called patrilineal. Toba Batak customs are connected by a red thread that is tied in a kinship relationship